UPAYA MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA MELALUI PEMANFAATAN ALAT PERAGA BERUPA BANDUL DAN STATIF PADA MATERI GETARAN DI KELAS VIII.2 SMP NEGERI 3 PEMULUTAN - Nora Aprilia (Universitas Sriwijaya, 2015)
The Problems that examined in this study is : Does the use of props in the form of the pendulum and the stand can increase student interest and learning outcomes VIII.2 grade SMPN 3 Pemulutan on the material Vibration? The purpose of this action research are: Increasing interest and student learning outcomes VIII.2 grade SMPN 3 Pemulutan through the use of props in the material Vibration 2014-2015 school year. This study used action research (action research) as much as two rounds. Each round consists of four phases: design, activities and observation, reflection, and refisi. Data obtained in the form of test results, students' interest observation sheet. From the analysis it was found that the achievement of learning outcomes of students has increased from cycle I to cycle II, namely, the first cycle (33.33%), Cycle II (79.16%). While the interests of students has increased from the first cycle there are only 4 people are quite interested in 16.66%, in the second cycle students' interest in emerging categories because there are 13 people that is 54.16%. The conclusion from this study is the use of props in the form of a pendulum and the stand on the matter could Vibration positive effect on interest and Student Results SMPN 3 Pemulutan.